Strategi Mengembangkan Perekonomian Desa melalui Penguatan Usaha BUMDES Unit Usaha Simpan Pinjam (U-USP) di Desa Parit Kebumen Kecamatan Rupat - Mulyadi Mulyadi; Rinah; Safriadi; Nur Azzatul Azura; Sindi Darma Fitri; Nurul Izzati; Nurul Ainni; Erzuraidah; Zainudin (Anotero Lembaga Scientific Pekanbaru, 2022)
The purpose of this research is to increase the capacity of the bumdes business through improving business management and initiating the establishment of new businessesThis study uses a qualitative descriptive research method that is useful for providing a detailed description of the Strategy for Developing the Village Economy through Strengthening the Bumdes Business Unit for Savings and Loans (U-USP) in Parit Kebumen Village, Rupat District.The results of the research. Community empowerment in developing the economy in Parit Kebumen Village is going pretty well, indicated by the existence of MSMEs in Parit Kebumen Village such as Handicraft Businesses, stalls, Shrimp Ponds, Rubber, Oil Palm, Coconut, Tofu, Tempe and public knowledge about MSMEs at this time do not fully know because the village community opens a business only to meet the daily needs of the Parit Kebumen village community and needs to be considered in managing MSMEs starting from aspects of financial management, human resources, operations and marketing.